2014
DOI: 10.1063/1.4894404
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the photovoltaic performance in P3HT: PbS hybrid solar cells using small size PbS quantum dots

Abstract: Articles you may be interested inIncreased open-circuit voltage in a Schottky device using PbS quantum dots with extreme confinement Appl. Phys. Lett. 102, 193902 (2013); 10.1063/1.4804614 Effect of ZnS coatings on the enhancement of the photovoltaic properties of PbS quantum dot-sensitized solar cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…At the time of the manuscript submission a paper by Firdaus et al has reported similar results with PbS QDs passivated by a benzenedithiol ligand. While this work reports a larger J SC , devices have a smaller FF .…”
Section: Discussionmentioning
confidence: 59%
“…At the time of the manuscript submission a paper by Firdaus et al has reported similar results with PbS QDs passivated by a benzenedithiol ligand. While this work reports a larger J SC , devices have a smaller FF .…”
Section: Discussionmentioning
confidence: 59%
“…Fig. 6 shows the room temperature intensity indicating efficient dynamics of exciton dissociation and subsequent hole transfer from the PbS NCs to the P3HT matrix before recombination [9,19]. The charge transfer is favoured due to the electron affinity difference between P3HT (À3.0 eV) and PbS (À3.8 eV).…”
Section: Elementmentioning
confidence: 96%
“…Overall photogenerated excitons increase and as a result the short circuit current density increases. The electron affinities of P3HT and PbS are À3.0 eV and À3.8 eV respectively, hence it is energetically favorable for electron transfer from P3HT to PbS and hole transfer from PbS to P3HT [9,26] as indicated in Fig. 7.…”
Section: Elementmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, the HOISC's properties depend strongly on the inorganic nanostructures, due to the carriers' interchange, geometry, composition and the absorption edge of the nanostructures used [2]. There are a lot of potential inorganic compounds suitable for HOISC, but metal oxides and chalcogenides are the most studied because of their appropriate optical properties [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%